The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3892/etm.2019.8224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin combined with metformin on serum cystatin C, homocysteine and maternal and neonatal outcomes in pregnant women with gestational diabetes mellitus

Abstract: Effects of insulin combined with metformin on serum cystatin C (Cys C), homocysteine (Hcy) and maternal and neonatal outcomes in pregnant women with gestational diabetes mellitus (GDM) were investigated. In total, 80 cases of pregnant women diagnosed with GDM in the Department of Obstetrics and Gynecology of Liaocheng Third People's Hospital from July 2015 to July 2017 were selected and divided into a study group (42 cases) and a control group (38 cases). The study group was treated with insulin combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…18,20 Previous studies have confirmed that the combined detection of Hcy and Cys-C can be used to predict adverse pregnancy outcomes in patients with GDM. 20,21 Our study demonstrates that adding GSP to Hcy and Cys-C combination further improve the reliability and sensitivity of the test and increase its predictive value for pregnancy outcomes in patients with GDM.…”
Section: Discussionmentioning
confidence: 78%
“…18,20 Previous studies have confirmed that the combined detection of Hcy and Cys-C can be used to predict adverse pregnancy outcomes in patients with GDM. 20,21 Our study demonstrates that adding GSP to Hcy and Cys-C combination further improve the reliability and sensitivity of the test and increase its predictive value for pregnancy outcomes in patients with GDM.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have confirmed that Cys C in serum of GDM patients can promote inflammatory response and aggravate vascular damage, which can be used to predict the prognosis of GDM patients and maternal and infant outcomes [ 11 ]. The increase of Hcy level can reduce the sensitivity of the body to insulin, which in turn increases the blood sugar level and increases the risk of maternal and infant complications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%